2006
DOI: 10.1080/00343400500450075
|View full text |Cite
|
Sign up to set email alerts
|

Income and employment disparities across European regions: The role of national and spatial factors

Abstract: Meliciani V. (2006) Income and employment disparities across European regions: the role of national and spatial factors, Regional Studies 40, 75-91. The paper analyses the impact of trends in employment rates on income convergence across European regions looking at the evolution of entire distributions. Between 1988 and 1996, European regions have been characterized by a very slow process of income convergence across countries and by a lack of income convergence within countries. While trends in labour product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
1
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 26 publications
4
27
1
1
Order By: Relevance
“…The simultaneous focus on productivity and employment variables also put focus on the relationship between the two in making up convergence in GVA per capita. Recently, some authors have suggested that there might be a trade-off between employment and productivity growth (Gordon 1995;McGuckin and van Ark 2005) and that this may lie behind slow European regional convergence rates in per capita GVA (Meliciani 2006). Meliciani especially argues that productivity increase have taken place in the least productive regions at the expense of employment by stating that "…increased competition through trade liberalization with low labour mobility can have forced convergence in labour productivity by means of a reduction of employment rates in low productivity regions" (2006, p. 88).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous focus on productivity and employment variables also put focus on the relationship between the two in making up convergence in GVA per capita. Recently, some authors have suggested that there might be a trade-off between employment and productivity growth (Gordon 1995;McGuckin and van Ark 2005) and that this may lie behind slow European regional convergence rates in per capita GVA (Meliciani 2006). Meliciani especially argues that productivity increase have taken place in the least productive regions at the expense of employment by stating that "…increased competition through trade liberalization with low labour mobility can have forced convergence in labour productivity by means of a reduction of employment rates in low productivity regions" (2006, p. 88).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the article analyzes whether there has been a trade-off between employment and productivity growth, as suggested by Meliciani (2006), and to what extent this potential trade-off is a distinctively European feature. For this purpose, a novel regional dataset that covers 89 Western European regions from 10 countries and 51 American states and districts has been put together.…”
Section: Introductionmentioning
confidence: 99%
“…Just as a short reference to some of the most interesting works, it is worth mentioning the old but excellent survey edited by Armstrong and Vickerman (1995). More recently, the books edited by Cuadrado-Roura and Parellada (2002) and Fingleton (2003), reviews as Magrini (2004), and papers such as those of López-Bazo et al (1999), Badinger et al (2004), Miller and Genc (2005), Fingleton and López-Bazo (2006), Meliciani (2006), Arbia et al (2008), Fischer and Stumpner (2008), and Mora (2008) are very good references.…”
Section: Introductionmentioning
confidence: 99%
“…The results, which are available upon request, show that, at large, mobility is lower with filtered than actual data, meaning that factors behind spatial dependence have a positive effect on intra-distribution mobility. 6 For more recent papers see, for instance,Meliciani (2006),Pittau and Zelli (2006),Ezcurra et al (2007),Villaverde and Maza (2008) and.…”
mentioning
confidence: 99%
“…Analysis of per capita convergence between countries has also been done by some authors: López-Bazo et al [14], Cuadrado and Parellada [15], Fingleton and López-Bazo [16], Badinger et al [17], Magrini [18], Miller and Genc [19], and Meliciani [20].…”
Section: Introductionmentioning
confidence: 99%